2020
DOI: 10.1101/2020.11.15.383372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Salmonellasubverts autophagy balancing bacterial fate and cellular inflammation

Abstract: SummarySalmonella Typhimurium (S. Typhimurium) is an enteric bacterium capable of invading a wide range of host cell types and adopting different intracellular lifestyles for survival. Host endocytic trafficking and autophagy have been implied to regulate the S. Typhimurium subcellular localization and survival. To reveal alternative host regulators on S. Typhimurium lifestyle, we combined a novel fluorescent reporter, Salmonella Intracellular Analyzer (SINA) with haploid forward genetic screening. This identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 46 publications
4
6
0
Order By: Relevance
“…In the absence of ATG16L1, the proportion of Δ sopF and WT bacteria accessible to the cytosol/in damaged vacuoles (CHQ resistance assay and Gal8 recruitment) were comparable, indicating that ATG16L1 contributes to the enhanced cytosolic access of ∆ sopF bacteria. Furthermore, it has been shown that interfering with LC3 conjugation by ATG3‐silencing (ATG3 functions in the step upstream of ATG5‐ATG12‐ATG16L1 in the autophagy cascade) reduced the levels of cytosolic Δ sopF bacteria in a similar manner to that seen in our ATG16L1 KO cell lines (Luk et al., 2020). In addition, we utilized SopF point mutants that fail to inhibit ATG16L1 recruitment to the V‐ATPase (Xu et al., 2019).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In the absence of ATG16L1, the proportion of Δ sopF and WT bacteria accessible to the cytosol/in damaged vacuoles (CHQ resistance assay and Gal8 recruitment) were comparable, indicating that ATG16L1 contributes to the enhanced cytosolic access of ∆ sopF bacteria. Furthermore, it has been shown that interfering with LC3 conjugation by ATG3‐silencing (ATG3 functions in the step upstream of ATG5‐ATG12‐ATG16L1 in the autophagy cascade) reduced the levels of cytosolic Δ sopF bacteria in a similar manner to that seen in our ATG16L1 KO cell lines (Luk et al., 2020). In addition, we utilized SopF point mutants that fail to inhibit ATG16L1 recruitment to the V‐ATPase (Xu et al., 2019).…”
Section: Discussionsupporting
confidence: 81%
“…2020 have also recently described residual LC3 conjugation to S . Typhimurium upon ATG3 knockdown in epithelial cells (Luk et al., 2020). Altogether, the data demonstrate that LC3‐conjugation on the SCV in epithelial cells requires, but is not absolutely dependent on, ATG3 and ATG16L1.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations